Reimagining care for adolescent and young adult cancer programs: Moving with the times. Issue 7 (5th February 2016) - Gupta, Abha A.; Papadakos, Janet K.; Jones, Jennifer M.; Amin, Leila; Chang, Eugene K.; Korenblum, Chana; Mina, Daniel Santa; McCabe, Lianne; Mitchell, Laura; Giuliani, Meredith E.
Abstract : Literature regarding the development of adolescent and young adult (AYA) cancer programs has been dominantly informed by pediatric centers and practitioners. However, the majority of young adults are seen and treated at adult cancer centers, in which cancer volumes afford the development of innovative supportive care services. Although the supportive care services in adult cancer centers are helpful to AYAs, some of the most prominent and distinct issues faced by AYAs are not adequately addressed through these services alone. This article describes how the AYA Program at Princess Margaret Cancer Centre has collaborated with existing supportive care services in addition to supplying its own unique services to meet the comprehensive needs of AYAs in the domains of: symptom management (sexuality and fatigue), behavior modification (return to work and exercise), and health services (advanced cancer and survivorship). These collaborations are augmented by patient education interventions and timely referrals. The objective of this article was to assist other centers in expanding existing services to address the needs of AYA patients with cancer. Cancer 2016;122:1038–1046. © 2016 American Cancer Society Abstract : Adult cancer centers may have resources that can be leveraged into programs for adolescent and young adult cancer care to optimize care delivery. Additional domains worthy of consideration for adolescent and young adult cancer programs include fatigue, exercise, sexual health, return to work, patient education, advanced cancers, and survivorship.